Synthesis, physicochemical studies, fluorescence behavior, and anticancer properties of transition metal complexes with the pyridyl ligand - Azam Mohammad; Al-Resayes Saud I. (Polish Journal of Chemical Technology, 2022)
A novel series of complexes with the formula [MLCl] [M = Co(II) (1), Ni(II) (2), Cu(II) (3), Zn(II) (4)] arising from Pyridyl ligand, N,N′-bis(1-(2-pyridyl)ethylidene)-2,2-dimethylpropane-1,3-diamine), ligand, L, was synthesized and investigated by elemental analyses, FT-IR, 1H and 13C NMR, Powder XRD, and thermal analyses. TGA analysis indicated that all complexes degraded in three different steps, while the PXRD examination showed well-defined sharp crystalline peaks for the complexes, indicating significant crystallinity. The antiproliferative activity of the ligand and its complexes were also evaluated in vitro against the HeLa (Human Cervical Cancer Cells) and HCT116 (Colon Cancer Cells) cell lines. The findings suggested complex 4 to be potential anticancer agent against these cell lines. In addition, ligand and its complexes also exhibited considerable emission properties.